Problems In Regulating Cohabitation as An Offense in Law Number 1 Of 2023 Concerning the Criminal Code - ikhsan, khairil (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2025)
This research discusses the problems arising from the criminalization of cohabitation in Article 412 of Law Number 1 Year 2023 on the Criminal Code (KUHP). Cohabitation, which is defined as living together without marital ties, is regulated as a criminal offense with prison or fine sanctions. This research uses normative legal research methods by examining laws and regulations, legal theories, and related expert opinions. The results show that the criminalization of cohabitation raises various problems, including violations of privacy rights, mismatch of sanctions with the character of the offense, as well as the potential for persecution and discrimination in law enforcement. In addition, this criminalization is considered not in line with the ultimum remedium principle, where criminal law should be the last resort in dealing with social problems. Article 412 of Law Number 1 Year 2023 on the Criminal Code (KUHP) is also considered unclear in formulating time limits and criteria for cohabitation, so it has the potential to be abused by law enforcement. This study concludes that the criminalization of cohabitation needs to be reviewed, by considering non-criminal approaches such as education and counseling, as well as respecting the right to privacy and the diversity of values in society. The recommendation of this research is the need for a more in-depth study of the social, psychological, and human rights impacts of criminalizing cohabitation, as well as a comparative analysis with similar regulations in other countries.